Determinants of customer perceived online shopping logistics service quality value: an empirical study from China. Issue 6 (2nd November 2019) - Han, Yunxia; Xie, Guangying
ABSTRACT: As a key component of electronic commerce, online shopping logistics service quality (OSLSQ) has received extensive attention in recent years. Many studies have focused on how to appraise and improve logistics service quality, while little research has been done on the potential value of improving OSLSQ. Based on 1236 questionnaires completed in Beijing, Wuhan, Changsha and Zhoukou, this paper contributes to the study of customer perceived value of OSLSQ by using an ordinal logit regression model. The results indicate that customer perceived value of OSLSQ varies across customers according to their age, education and location, but no difference is found between males and females. In addition, customer perceived value is closely linked with customer satisfaction.